Aminophylline for treatment of postdural puncture headache: A randomized clinical trial. (24th April 2018) - Wu, Chuanjie; Guan, Dongsheng; Ren, Ming; Ma, Zhengfei; Wan, Changming; Cui, Yinglin; Zhong, Ping; Zhao, Wenbo; Li, Chuanhui; Yan, Feng; Xie, Jinqiu; Xue, Fang; et al.
Abstract : Objective: To investigate the efficacy and safety of IV aminophylline for patients with postdural puncture headache (PDPH). Methods: We randomly assigned patients to groups receiving either 250 mg IV aminophylline or a placebo within 3 hours of symptom onset once daily for 2 consecutive days. The primary endpoint was headache severity 8 hours after treatment. We assessed this using visual analog scale (VAS) scores taken from patients in a standing position. We also recorded posttreatment VAS score changes, Patient Global Impression of Change (PGIC) scores, and adverse events. We performed an intention-to-treat analysis. Results: We enrolled 126 patients with PDPH at 5 centers in China (62 assigned to the aminophylline group and 64 to the placebo group). The median age was 37 years, and 96 (76.2%) patients were women. Compared to the placebo-treated patients, the aminophylline-treated patients had significantly lower mean VAS scores 8 hours after treatment (5.34 vs 2.98, p < 0.001) and were significantly more likely to report improvements on the PGIC (39.1% vs 72.6%, p < 0.01). This therapeutic effect was already evident at the 30-minute time point and persisted for 2 days. There was no significant difference in the incidence of adverse events (4.8% vs 1.6%, p = 0.589). Conclusions: IV aminophylline is an effective and safe early-stage treatment for patients with PDPH. ClinicalTrials.gov identifier: NCT02522013. Classification of evidence: This study provides Class I evidence that for people with PDPH, IV aminophylline reduces headache severity.